Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Pada Bidang Pelayanan Penempatan Tenaga Kerja di Dinas Tenaga Kerja dan Transmigrasi Kabupaten Kabupaten Bantul Daerah Istimewa Yogyakarta - Wilis Fahlefi (Jurnal Bisnis, Manajemen, dan Akuntansi, 2021)
The purpose of this study was to determine the effect of the quality of public services on community satisfaction in the field of labor placement services at the Manpower and Transmigration Office of Bantul Regency, Special Region of Yogyakarta. Sampling in this population uses a non-probability sampling technique with the type of accidental sampling. The population of people who visited the Manpower and Transmigration Office of Bantul Regency, D.I.Yogyakarta, was 50. The sample taken was 44. Data was collected by distributing questionnaires to respondents. The collection technique using SPSS.17. Based on the results of the study, it was stated that the Public Service Quality variable had a positive and significant effect on community satisfaction, having a significant value of 0.000 <0.05.